2015
DOI: 10.3390/v7010333
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hantavirus Infection and Selenium Deficiency in Mainland China

Abstract: Hemorrhagic fever with renal syndrome (HFRS) caused by hantaviruses and transmitted by rodents is a significant public health problem in China, and occurs more frequently in selenium-deficient regions. To study the role of selenium concentration in HFRS incidence we used a multidisciplinary approach combining ecological analysis with preliminary experimental data. The incidence of HFRS in humans was about six times higher in severe selenium-deficient and double in moderate deficient areas compared to non-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…In China, HFRS is listed as a class B notifiable infectious disease, and cases diagnosed at medical institutions are required to be reported to CCDC through the national Notifiable Infectious Diseases Reporting Information System 33 . The case definition of HFRS is according to the guidelines of the World Health Organization (WHO).…”
Section: Methodsmentioning
confidence: 99%
“…In China, HFRS is listed as a class B notifiable infectious disease, and cases diagnosed at medical institutions are required to be reported to CCDC through the national Notifiable Infectious Diseases Reporting Information System 33 . The case definition of HFRS is according to the guidelines of the World Health Organization (WHO).…”
Section: Methodsmentioning
confidence: 99%
“…In the Mekong Delta of Vietnam, rodents can be infected with DOBV and SEOV with a positive rate of 6.9% (Van Cuong et al, 2015). There have also been studies claiming that selenium deficiency is correlated with increased prevalence of hantavirus infections in both humans and rodents (Fang LQ et al, 2015).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
“…Although the HV carriage rates among rodents in Regions b and c were higher than that associated with Region a, the severity of the epidemic situation was less severe, suggesting that the HV-susceptible population appears to be more susceptible to the HV strains in Region a (which mainly belong to the HTNV genotype). Interestingly, the distance between Regions b and a is much smaller than that between Regions b and c. Despite this, the epidemic characteristics of Region b are quite different from those of Region a, and more similar to those of Region c. Although previous studies have shown that HTNV (which was the main genotype in Region a, where the epidemic situation was more serious) is more harmful to humans than SEOV (which was the main genotype in Regions b and c), local geographic conditions, climate, HFRS prevention and control measures and safety awareness among susceptible populations are also important factors[15,2529]. Therefore, we believe that a further study should be performed to explore the factors underlying our result.…”
Section: Discussionmentioning
confidence: 99%
“…The data on S and M segments in this study were insufficient, so the phylogenetic analysis of HV may be biased. Second, there are many factors that can influence the distribution and severity of infectious disease, such as natural environmental factors, urbanization processes and local prevention efforts[2931]. However, this research lacked information on these factors, so the HFRS spatio-temporal distribution analysis is inadequate.…”
Section: Discussionmentioning
confidence: 99%